Efektifitas Edukasi Berbasis Family Centered Maternity Care terhadap Dukungan Keluarga dan Self Efficacy pada Ibu Postpartum dalam Pemberian Asi - Winarti, Gusti; Nasution, Siti Zahara; Siregar, Farida Linda Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the effectiveness of family centered maternity care-based education on family support and self-efficacy for postpartum mothers in breastfeeding. The method used is quantitative research with a quasi-experimental design with a pretest and posttest design with a control group. The sample in this study consisted of 52 respondents. The research instrument used a family support questionnaire modified from Nasution's family support questionnaire (2007) and a self-efficacy instrument using the Breastfeeding Self-efficacy Scale-Short Form (BSES-SF). Data analysis used the Paired T-Test and Independent T-Test. The results of research on the effectiveness of interventions on family support, P-Value 0.000 and self-efficacy 0.004. The conclusion is that education based on Family Centered Maternity Care is effective in increasing family support and self-efficacy for postpartum mothers in breastfeeding. Keywords: Education, Family Support, Family Centered Maternity Care, Self efficacy